Field performance of conventional vs in vitro propagules of plantain (Musa spp., AAB group) - Vuylsteke, D.R.; Ortíz, R. (1996)
In vitro-propagated plants of plantain (Musa spp., AAB group) did not manifest consistently superior horticultural performance compared to conventional propagules. Tissue culture plants grew vigorously and taller than sucker-propagated plants, but higher yield was not obtained, probably because of severe disease and suboptimal husbandry input. Phenotypic variation was higher in tissue culture plants, although this increase was not always statistically significant. There were no other detrimental effects of in vitro propagation on field performance. Botanical seed set rates for the two types of propagules were similar. The advantages of tissue-culture-derived plants as improved planting material would be most relevant for establishing field nurseries for further clean, conventional propagation of newly bred or selected genotypes.